0537 Cognitive Functioning Before and After Insomnia Treatment in Women Veterans. (27th May 2020) - Dzierzewski, J M; Zhu, R; Donovan, E K; Perez, E; Song, Y; Kelly, M R; Carlson, G; Fung, C H; Alessi, C; Martin, J L
Abstract: Introduction: Women are at higher risk for cognitive impairment and dementia compared to men. Identifying potentially treatable risk factors such as insomnia is an important clinical goal. In a trial comparing two behavioral treatments for insomnia in women veterans, we hypothesized that 1) worse baseline insomnia severity would be associated with poorer cognitive function, and 2) improvement in insomnia severity with treatment would be associated with improvement in cognitive functioning. Methods: 347 women veterans with insomnia disorder [mean age 48.3 (12.9) years] completed baseline testing. Of these, 149 women were randomized to receive cognitive behavioral therapy for insomnia (CBT-I) or acceptance and commitment (ACT) based insomnia treatment (both treatments included sleep restriction, stimulus control, and sleep hygiene). Insomnia Severity Index (ISI) was assessed at baseline, post-treatment, and 3-month follow-up. Cognitive functioning was measured with Symbol Digit Coding (SDC) and Trail Making Test A and B (TMTA and TMTB). Pearson correlations were used to examine associations between insomnia severity and cognitive functioning at baseline and changes in both insomnia severity and cognitive functioning from before to after treatment. Results: At baseline (N=347), mean ISI was 14.1 (5.3). Worse baseline ISI was associated with worse baseline cognitive functioning on TMTA (r=-.15, p<.01) and SDC (r=-.12, p<.05). In the randomized sample (N=149), ISI scores improved at post-treatment (mean ISI change= -9.0; p<.001) and 3-month follow-up (mean change= -8.0; p<.001) relative to baseline. Improvement in ISI from baseline to post-treatment was significantly associated with improvement in SDC from baseline to post-treatment (r=-.18, p<.05), but not improvement in TMTA and TMTB. Change in ISI was not significantly related to change in cognitive tasks from baseline to 3-month follow-up. Conclusion: More severe insomnia is associated with worse cognitive functioning in women veterans. The magnitude of improvement in insomnia symptoms may be associated with improvement in cognition. Support: NIH/NIA K23AG049955 (PI: Dzierzewski); VA/HSR&D IIR-HX002300 (PI: Martin), NIH/NHLBI K24HL143055 (PI: Martin).